De Vega annuloplasty versus ring annuloplasty for repair of functional tricuspid regurgitation - Alnawaiseh, Khaled; Albkhoor, Bashar; Alnaser, Yanal; Aladwan, Hayel; Ghanma, Issa (International Journal of Research in Medical Sciences, 2018)
Background: Tricuspid insufficiency (TI) is a functional insufficiency in most of the cases and associated with the dilatation of the annulus and remolding. Pulmonary hypertension and right ventricular volume overload due to chronic aortic or / and mitral valve disease in most of the time causes the functional tricuspid insufficiency. Despite the different techniques used to repair the tricuspid valve, the recurrent TR is still occurring in 20- 30 % of the patients and the development of late TR is an important complication of left heart surgery. Our study aims to compare the long-term outcome of ring annuloplasty with De Vega annnuloplasty in patients with secondary tricuspid regurgitation (TR). Methods: A retrospective study of 320 patients who underwent tricuspid valve repair surgery for secondary tricuspid regurgitation from January 2002 to December 2010 at Queen Alia Heart Institute (QAHI). Patients were divided into two groups, in group (1) (n=180) patients had an annuloplasty ring. Group (2) (n=140) patients had De Vega procedure (no ring). The procedures were performed in association with mitral valve surgery in 78% of patients, aortic valve surgery in 15% and combined aortic and mitral valve surgery in 7% of patients. TR grade, NYHA functional class and Pulmonary artery pressure were nearly similar and no significant preoperative difference between the two groups. Results: Echocardiographic and clinical follow up were done for all patients. The duration of procedure for both De Vega and ring annuloplasty were nearly similar. The overall survival in ring group at 5year was 83.9% versus 77.9% in De Vega group. Freedom from residual and recurrent TR, event free survival and long-term survival were significantly better in the ring group and also the tricuspid valve reoperation were less in the ring group. Conclusions: The implantation of annuloplasty ring results in lower incidence of residual or recurrent of tricuspid regurgitation, improved the event-free survival and long-term survival when compared with the sewing techniques such as De Vega.